2023
DOI: 10.1002/cae.22611
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of open‐source software in teaching the physics of P‐N diodes

Abstract: This paper describes utilizing open-source numerical simulation software, typically used in solar photovoltaics research, as an attractive supplementary educational tool for teaching the underlying physics and operation of P-N junction diodes. Details of educational P-N device models and simulationbased learning scenarios developed for this purpose are provided here. The presented approach allows students to learn the essential concepts related to P-N diodes experientially. These include some frequently observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Using the finite element method, PC1D solves this nonlinear partial differential equation system in one dimension with the appropriate boundary conditions derived from the device's realistic operational conditions. This approach has proven robust and accurate for various devices [27,[35][36][37][38], including InPbased solar cells [39][40][41]. The simulations presented here are based on Boltzmann charge carrier statistics, recommended when implementing the default bandgap narrowing model in the simulations:…”
Section: Numerical Modeling and Simulation Methodologymentioning
confidence: 99%
“…Using the finite element method, PC1D solves this nonlinear partial differential equation system in one dimension with the appropriate boundary conditions derived from the device's realistic operational conditions. This approach has proven robust and accurate for various devices [27,[35][36][37][38], including InPbased solar cells [39][40][41]. The simulations presented here are based on Boltzmann charge carrier statistics, recommended when implementing the default bandgap narrowing model in the simulations:…”
Section: Numerical Modeling and Simulation Methodologymentioning
confidence: 99%
“…Wang, J. et al used questionnaires and other methods to explore the impact of teaching methods on students' learning of physics models and modeling skills based on modern teaching techniques in a flipped classroom approach and demonstrated that model-based flipped classroom supported by modern teaching techniques could enhance the efficiency of physics teaching through aligned experiments [11]. Alnassar, M. S. N. used open-source numerical simulation software for teaching the basic physics and operation of P-N connected diodes to solar photovoltaic research and complements the implementation of this tool for rigorous physics teaching [12]. Mircik, K. S. A.…”
Section: Introductionmentioning
confidence: 99%